Organic linseed (Tisi) farming: a step towards doubling farmers’ income - Singh, S. K.; Manibhushan, Manibhushan; Kumar, Ajay (Indian Farming, 2018)
Linseed is nutritionally rich and have many health benefits for organic production. It can be grown in marginal lands under different agroclimatic conditions of India with assured harvest. It is short duration, drought resistant, easy for cultivation with limited external inputs, fewer pests and diseases and long storability of grains without store pests damage are unique qualities and hence can be a step forward for doubling the income of farmers in india.